Autonomous Schools, Achievement, and Segregation - Natalie Irmert; Jan Bietenbeck; Linn Mattisson; Felix Weinhardt (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study whether autonomous schools, which are publicly funded but can operate more independently than government-run schools, affect student achievement and school segregation across 15 countries over 16 years. Our triple-differences regressions exploit between-grade variation in the share of students attending autonomous schools within a given country and year. While autonomous schools do not affect overall achievement, effects are positive for high-socioeconomic status students and negative for immigrants. Impacts on segregation mirror these findings, with evidence of increased segregation by socioeconomic and immigrant status. Rather than creating "a rising tide that lifts all boats," autonomous schools increase inequality.
Keywords: I21; I24; J15; 330; autonomous schools; student achievement; school segregation